Analysis of the Office Location Selection Strategy at PT. Bank Sumut - Rambe, Ansari Abror; Siregar, Nurintan Asyiah (PT FORMOSA CENDEKIA GLOBAL, 2024)
Bank Sumut is a regional government-owned enterprise (BUMD) of North Sumatra Province, operating in the financial services or banking industry. As a financial institution owned by the regional government, Bank Sumut must implement specific strategies to compete with other banking institutions. In determining its office location strategy, Bank Sumut takes several factors into account, including government centers, markets, public facilities, residential areas, and office locations. This approach enables Bank Sumut to better execute its competitive advantage, particularly in the regional financial sector, by targeting potential market segments more effectively. Additionally, Bank Sumut has a distinctive approach in determining the hierarchy of its office units, including the Head Office, Regional Branch Offices, Branch Offices, Sub-Branch Offices, and Cash Offices, ensuring easier access for the public to banking services and the products offered by Bank Sumut.